Western European Public Opinion on Defense-A Return to Better Red Than Dead?. - United States. International Communication Agency. Office of Research.; Crespi, Leo Paul, 1916-2008. (Tufts University. Tisch Library., 2019)
In the intense reconsideration of the role of nuclear weapons presently taking place in Western Europe, an old slogan-"Better Red Than Dead"-has once again arisen. To probe the extent of this sentiment among the general public in Western Europe, the International Communication Agency (USICA) recently conducted surveys in Great Britain, France, Italy, and West Germany. The results of the surveys (see table, page 4) show that the direction in which we are heading in Western defense-the use of tactical nuclear weapons to counter Soviet conventional threat-may be exactly what the Western European public will not accept.